Torsional Hopkinson Bars testing : increase input loading torque strength - Seet, Boon Hwee. (2011)
This primary objective of this Final Year Project (FYP) is to increase the input loading torque strength in order to prove the theoretical existence of the research study. The Torsional Split Hopkinson Bar (TSHB) apparatus was used for the experiment. The main focus was to the tightening of the bar prior to the experiment and the various ways of doing so. In the course of the experiment, investigation findings were gradually obtained through various methodologies in sourcing the actual root cause. In additional, the report included the theory of the setting up of TSHB apparatus and experiment procedure with further experiment processes that were introduced to allow better understanding of the respective system. The ways of narrowing down to the final objective was also included with the improvement to the clamping design tightness of the torsion bar. In conclusion, the torsion theory and the experiments conducted were used to verify the relationship that causes discrepancy to the actual finding that was obtained. The theoretical finding is present but the result varies with the actual practical experiment as compared. With further hindrance of the components used, only the theoretical studies produce could be presented. The inability of the apparatus to transmit practical finding could be attributed by frictional issues pertaining to worn apparatus.